El Derecho de la Competencia en la Comunidad Andina de Naciones – can. Análisis y propuestas - Miranda Londoño, Alfonso (2022)
This paper briefly explains the Andean Community of Nations antitrust law, its development, background, exercise, procedure and relevance facing the current regulations. The free economic competition phenomenon has been a result of the free trade, the agreements between the countries and the globalization. This has led to the implementation of a European-style supranational competition regime in the Andean Community of Nations, with an authority that investigates and sanctions, a tribunal in charge of the judicial control and a legislative body. Although this structure seeks to promote the commercial cooperation, there are some difficulties in the way the competitive activity behaves in the sector. Some of the difficulties are the free movement of goods, services, and capital in the territory of the Andean community and the creation of macroeconomic and investment policies that may affect the application of the antitrust regime. This leads the economic agents to develop cross-border anticompetitive behaviors. Therefore, the antitrust law of the Andean Community of Nations should be upgraded in: The jurisdictional activation of the authorities, the requirements to open an investigation, the definition of anticompetitive conducts and their effects, the introduction of a Leniency Program that can harmonize with national legislations and the creation of a merger control regime. The last suggestions are presented in the final part of this paper.